Digital Anthropometer Development for Improving the Measurement Quality of Human Body Dimensions - Trio Yonathan Teja Kusuma; Arya Wirabhuana; Faurosi Syafa’atul Yusuf (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2019)
Digital information technology has become the nerve of information for industry-based companies. However, there are still data or information that retrieved manually, one of them is measurement of the human body dimension. The problem is seemed solved by invention of digital anthropometer application. Yet, the application requires a further improvement especially in its accuracy and user interface. The improvement of accuracy quality of its measurement uses the capability process analysis method. As a result, the current Cp and Cpk is 0.26 and -0.209 while in the developed application is 2.56 and 1.218. Thus, the developed application is stated that quality of measurement increases to meet the criteria of good process capability. The user interface is improved based on the user voices. Data storage databases and percentile calculation in the application was added as one on the significant user-interface improvement.